Large-scale DNA barcoding reveals cryptic diversity in eulophid wasps (Hymenoptera, Chalcidoidea, Eulophidae) - Emma Kärrnäs; Christer Hansson; Niklas Wahlberg (Arthropod Systematics & Phylogeny)
Abstract Despite their ecological and economic importance as key regulators of insect populations worldwide, eulophid wasps remain one of the taxonomically most neglected groups of insects. As these minute parasitoid wasps exhibit an astonishing species diversity while being challenging to identify, relying on morphological characters alone has long been problematic. By using large-scale barcoding and molecular species delimitation analyses of 909 specimens, of which 641 were of European origin, we reveal a remarkable diversity of cryptic species in the two eulophid wasp genera Oomyzus Rondani and Quadrastichus Girault (Eulophidae, Tetrastichinae) present in Europe. We also present 40 new country records for 17 species and greatly improve the existing DNA barcode libraries of these two groups. Using the four different species delimitation methods ABGD, ASAP, GMYC and mPTP, the number of potentially undescribed European species detected in this study ranges from 20 to 34, of which 16 to 24 are cryptic. These results suggest that not even half of the European Oomyzus and Quadrastichus species are currently known, thus highlighting the need for further taxonomic work. However, the results also highlight issues with molecular species delimitations based on barcode data, such as incongruence across different analysis methods and potential barcode sharing between closely related species. Therefore, the results also challenge the validity of relying on a single molecular marker when detecting and subsequently describing new species, an increasing practise within modern taxonomy termed “turbo-taxonomy”.